Relationship Between The Level of Alcohol Consumption to The Depression of Multiple Substance Users in Sleman Yogyakarta - Kusumadewi, Andrian Fajar; Daniswara, Pambayung Caesaria Tiara; Ismanto, Silas Henry; Aulia, Afkar (Biomedical Journal of Indonesia, 2020)
Introduction: The problem of using addictive substances, especially alcohol in Indonesia, is still a serious health problem. Since 2013, data on the proportion of alcoholic drink consumption in Indonesia has been found to have increased in 32 provinces in Indonesia. Alcohol consumption not only causes physical problems, but also mental disorders, triggers acts of violence, and disturbs other aspects of life. One of the psychiatric disorders that arise due to the abuse of alcoholic beverages is depression. If not treated immediately, depression can lead to suicidal thoughts that threaten the individual and have an impact on those around him. The aim of this study was to examine the level of alcohol consumption and its relationship to the level of depression. Methods: This study is an analytical study with a quantitative cross-sectional survey design. The sampling technique was carried out by purposive sampling using the AUDIT questionnaire for the level of alcohol consumption, and BDI-II for the level of depression. Results: The research sample was obtained as many as 30 respondents. The results of the two-variable analysis using the somer test showed that there was no significant relationship between the level of alcohol use and the level of depression. Conclusion: In this study, there was no statistically significant relationship between the level of alcohol use and the level of depression in individuals who used multiple substances.